Helping a Neighbour in Need: An Auto-ethnography of Lived Hadith Citizenship - Rizwan Sahib (Jurnal Living Hadis, 2021)
This study presents specific ahadīth (sing. hadīth) which inform neighbourly relations on a day-to-day basis. I interpret my actions towards a neighbour, who was experiencing personal problems, as lived-hadīth citizenship. That is, my interactions with my neighbour were infused with Prophet Muhammad's teachings and instructions as found in ahadīth. Aspects of Prophetic wisdom, such as care and easing somebody’s burdens, align with contemporary sociological, anthropological, and psychological definitions of citizenship. This study thus shows that Islamic scripture has a positive role to play in Western societies, shaping daily behaviours such as being a good citizen in one’s neighbourhood.